(untitled) (Global Journal of Human-Social Science, 2020)
There are many different definitions of cosmopolitanism and nationalism Each of these terms cannot have one precise definition because there are many theories principles and issues that overlap in defining the terms To define both cosmopolitanism and nationalism one may have to consider factors like border-crossing individ Nationalsmualism citizenship or international justice Kaunonen 23 Cosmopolitanism may incorporate aspects of nationalism and therefore there interrelationship that comes into play when giving a compressive definition to these terms Cosmopolitanism involves wide range views on moral and socio-political beliefs and practices Initial shared thought about cosmopolitanism suggested that all humankind regardless of their different affiliations should exist as one community With time different views have created different versions of cosmopolitanism either based on moral customs political alignments or geographical influences Philosophical roles have always centered on cosmopolitanism debate Cosmopolitanism arguments have always revolved around breaking bonders and other human interaction limitations The scope of defining people in a dimension of world citizenship brings into light the ideological concept of cosmopolitanism